2019
DOI: 10.18775/jibrm.1849-8558.2015.46.3005
|View full text |Cite
|
Sign up to set email alerts
|

The Performance Effect of Dynamic Capabilities in Servitizing Companies

Abstract: As an increasing number of companies operates in international markets characterized by global competition, many traditional manufacturers augment their product offerings with services to gain competitive advantage. As servitization needs change throughout the company, many companies struggle on the transition from a product – to a service centric business model. The dynamic capabilities view analyses capabilities in changing environments and could therefore be an interesting theoretical lens for servitization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The NFP items used in this research are reputation level (NFP1), level of customer satisfaction (NFP2) and level of customer retention (NFP3). These non-financial items were selected from the literature review and empirical studies (Tempelmayr et al , 2019; Schilke, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The NFP items used in this research are reputation level (NFP1), level of customer satisfaction (NFP2) and level of customer retention (NFP3). These non-financial items were selected from the literature review and empirical studies (Tempelmayr et al , 2019; Schilke, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the inconclusive evidence from the literature (Hamsal et al , 2022), the results of H6 confirm this proposition, given the positive relationships identified between organizational resilience and financial performance. In service organizations, the financial base that can facilitate the development of service-centric business models (Tempelmayr et al , 2019) postdisruption is contingent more on organizational resilience than dynamic capabilities, though the latter is an enabling factor of organizational resilience. Collectively, these findings extend the management (Argote and Ren, 2012; Cotta and Salvador, 2020; Duchek, 2020; Fernandez-Giordano et al , 2022; Hamsal et al , 2022) and marketing (Martin and Bachrach, 2018) literature by establishing a TMS as an antecedent of dynamic capabilities and organizational resilience, with positive consequences on financial performance during a disruptive event such as the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Battisti and Deakins (2017) confirmed that changes to the firm's resource base due to disasters have a positive effect on financial performance. In exploring firms that are moving from a product-centric to a service-centric business model, Tempelmayr et al(2019) found a positive relationship between sensing and reconfiguration but not seizing on firm performance. Despite the mixed evidence, we propose:…”
Section: H4mentioning
confidence: 99%
“…It is crucial for all manufacturing firms to serve its customers by creating value for them and, by doing so, build a long-lasting competitive advantage (Battistella et al, 2017;Koufteros et al, 2002). This is achieved by identifying, developing and continuously improving the most essential manufacturing capabilities, in other words, working with manufacturing strategy implementation (Sansone et al, 2020a;Slack and Lewis, 2019;Tempelmayr et al, 2019). The core of a competitive advantage lies in the ability to differentiate from competitors through products or services and in the ability to operate at a lower cost by using less resources (Christopher, 1998).…”
Section: Manufacturing Strategy Capabilities and Performancementioning
confidence: 99%